Synthesis of heterobimetallic gold(I) palladium(II) bis(acyclic diaminocarbene) complexes via the isonitrile route - Dietl, Martin C.; Vethacke, Vanessa; Keshavarzi, Ali; Mulks, Florian; Rominger, Frank; Rudolph, Matthias; Mkhalid, Ibraheem A. I.; Hashmi, A. Stephen K. (Organometallics, 2022)
A convenient one-pot approach to bridged heterobimetallic gold(I) palladium(II) bis(acyclic diaminocarbene) complexes is presented. The methodology exploits the graduated nucleophilicities of aliphatic and aromatic amines connected via an aromatic unit. This enables a straightforward access to bridged complexes from easily available isonitrile metal precursors.